PENYAMPAIAN PESAN DIGITAL MARKETING TOKO ONLINE DANVISTORE - Amini, Rizki Fadila; Rohimah, Afifatur; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2019)
The development of technology comes as a solution to facilitate activities, everything and everyone can connect quickly. This is what causes online business more and more in demand. Danvistore is a business that sells apple products and markets its products through an online shop. In the midst of a very tight online business, Danvistore delivered several effective messages to attract consumer buying interest so as to increase sales. The purpose of this study was to determine the delivery of digital marketing messages by the online store Danvistore.This research uses descriptive qualitative method, by collecting data through interviews and documentation. The theory used by researchers is the theory of effective message delivery and the benefits of digital marketing. The speakers of this research are Danvistore shop owner and two consumers from Danvistore. The results of this study indicate that Danvistore applies three elements of the six elements of digital marketing namely target marketing, information access and also sales potential. And applying the nine elements of the eleven elements of effective message delivery, among others, messages attract attention, messages create interest, messages create trust, messages remember, messages provide information, messages teach, persuading messages, messages that create brand associations, and messages that trigger action. All done as an effort to increase sales.Keywords: Digital messaging, online communication, online shop